How synchronous learning changes the workload of teachers: Experiences learned from expanding countries - Masykuri, Edi Sunjayanto; Alekseevna, Ekaterina Konstina; Nikitina, Alena Yurevna; Petrovna, Olga Alexandrovna; Purwoko, Riawan Yudi (LPPM Universitas Muhammadiyah Purworejo, 2024)
The Impact of synchronous Learning on Educators' Workload The coronavirus outbreak, particularly in the Republic of Indonesia and the Russian Federation, has fundamentally altered the teaching and learning process. The in-person teaching and learning process transitions to an online format. Educators and learners must be prepared for execution. Educators must adapt their instructional methods for online platforms to ensure the continuity of teaching and learning. This presents significant obstacles and obligations, particularly for educators who are initiating the online teaching process. This study aimed to ascertain if Synchronous Learning exacerbates the physical, mental, and financial burdens on teachers. The employed methodology was quantitative, utilizing an online-distributed questionnaire as the tool. The research samples comprised 20 educators employed at private senior vocational institutions in Indonesia and Russia. The teacher burdens variable indicates that the average responder perceives the burden as high, as seen by an average value of 0.730, which falls within the range of 0.501 to 1. This concludes that Synchronous Learning significantly increases instructors' workloads. It proves that synchronous learning imposes additional physical, emotional, and financial burdens on teachers.